2016
DOI: 10.1007/s13277-016-4948-7
|View full text |Cite
|
Sign up to set email alerts
|

Clinical impact of circulating microRNAs as blood-based marker in childhood acute lymphoblastic leukemia

Abstract: Aberrant microRNA (miRNA) expression participates in childhood acute lymphoblastic leukemia (ALL). This study aimed to investigate the expression of miRNA-100, miRNA-196a, and miRNA-146a among childhood ALL and study their correlation with other hematological parameters and different phenotypes. Peripheral blood mononuclear cells (PMNCs) were obtained from 85 childhood ALL and 25 healthy children for the detection of miRNA expression using quantitative real-time PCR. Significant higher median levels were repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 24 publications
0
23
0
Order By: Relevance
“…19 Regarding the prognosis, a high level of miR-155 is a predictor of a bad prognosis in patients with CLL 8 and AML. [20][21][22][23] miR-155 has a clear association with lymphomas and leukemias pathogenesis, progression, and response to treatment. At the same time, it has a direct relation with the immune response to HCV infection and its replication and response to treatment as well.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Regarding the prognosis, a high level of miR-155 is a predictor of a bad prognosis in patients with CLL 8 and AML. [20][21][22][23] miR-155 has a clear association with lymphomas and leukemias pathogenesis, progression, and response to treatment. At the same time, it has a direct relation with the immune response to HCV infection and its replication and response to treatment as well.…”
Section: Introductionmentioning
confidence: 99%
“…Patients who achieved complete remission showed low levels of miR‐155 in the plasma . Regarding the prognosis, a high level of miR‐155 is a predictor of a bad prognosis in patients with CLL and AML …”
Section: Introductionmentioning
confidence: 99%
“…The characteristics of the studies included are shown in (Table 1). 16,17,19–24,28,29,3544 A total of 1,389 haematological cancer patients (433 leukaemia, 391 lymphomas and 565 MM) and 1013 healthy controls were investigated. In all studies, quantitative real-time chain reaction polymerase (qRT-PCR) tests were used to detect expression levels of miRNAs in either plasma (n=28) or serum (n=22).…”
Section: Resultsmentioning
confidence: 99%
“…In ALL, a few circulating miRNAs were recently described, and among them miR-146a. Significant higher median levels of miR-100, miR-196a, and miR-146a were reported in blood samples of affected children compared to controls, but the diagnostic efficacy for miR-146a analysis presented superior sensitivity and specificity [ 211 ]. These same authors recently reported the significant increased expression of circulating miR-125b-1 and low levels of miR-203 in serum samples from untreated newly diagnosed children with ALL ( n = 43), as detected by quantitative RT-PCR analysis [ 212 ].…”
Section: Mirnas In Clinicsmentioning
confidence: 99%